DEATH PENALTY AS AN AFFRONT TO HUMANITY AND GLOBAL CIVILISATION: NIGERIA AS A CASE STUDY (UCC Law Journal, 2022)
The death penalty in Nigeria and indeed all over the world has become a subject of perpetual discourse. This is because protagonists and antagonists are at each other throats on the need for its retention or abolition. It is a thorny and emotional controversy that has not shown any sign of abating. The issue of death penalty transcends regional divide, political ideology, race and civilisation. This piece is an appraisal of death penalty application in Nigeria and its continued relevance in view of the dominant global pulse of human rights, recent positive developmental strides in the areas of civilisation and the error prone criminal justice system. The paper using doctrinal research methodology finds that the 1999 Constitution of the Federal Republic of Nigeria (as amended) does not prohibit its application. The study however finds that there is changing perception of crimes and punishment globally. As a result, international law is becoming paternalistic-moving towards the abolition of death penalty. The study therefore is a clarion call to the law makers to roll back the provision of death penalty and adopt life jail as a viable alternative. By so doing, Nigeria will not trail behind international trends in human rights and civilization. It will also make her stand on a higher pedestal than the depraved offender.